Einstein A coefficients for rovibronic lines of the A2Π → X2Σ+ and B2Σ+ → X2Σ+ transitions of CaH and CaD. Issue 1 (13th October 2017) - Alavi, S. Fatemeh; Shayesteh, Alireza
Abstract: Calcium monohydride is an important diatomic molecule appearing in the spectra of sunspots and M dwarfs. We report complete line lists with Einstein A coefficients for the A 2 Π– X 2 Σ + and B 2 Σ + – X 2 Σ + electronic transitions of CaH and CaD radicals. The most recent ab initio transition dipole moments and potential energy curves were used for the calculation of vibronic band intensities, taking the Herman–Wallis effect into account, and the rotational line strengths were calculated using the pgopher program of Western. For the A 2 Π and B 2 Σ + excited states of CaH and CaD, new off-diagonal electronic matrix elements were included in the Hamiltonian matrix, and new sets of spectroscopic constants were determined in order to accurately reproduce the line positions and relative intensities of the observed branches in laboratory spectra. For both CaH and CaD isotopologues, Einstein A coefficients were calculated for all possible rovibronic transitions from the v ΄  = 0–3 vibrational levels of the A 2 Π state and the v ΄  = 0–2 vibrational levels of the B 2 Σ + state to the v ″  = 0–4 vibrational levels of the X 2 Σ + ground state. The line lists and intensities reported here can be used to accurately determine the amounts of CaH and CaD in stellar environments.